Key Technology Research on Metal Structure of Datengxia Spillway Gate - YUAN Wei; FAN Xiaofu; QI Qige (Renmin Zhujiang)
Using the main dam of the Datengxia Hydro Project as a background,a brief introduction to the metal structure arrangement of the spillway gate.The sluice gate has a large number of discharge holes,large size,frequent operation,high drainage control requirements,and very complex hydraulics conditions.In order to ensure the flood discharge building operation safe and reliable,through the model test and three-dimensional finite element analysis,solve the discharge sluice arc gate flow shock vibration,low hole arc door support structure analysis and other key technical problems,optimize the structure design of the equipment,made clear about the discharge sluice metal structure equipment safety local open height,improve the reliability of the normal operation of the hub.Especially the design of the low hole arc gate,its orifice size and design head and other technical indicators are in the forefront of the country,has a reference to the same type of project.